Pro Silverlight 4 in VB - MacDonald, Matthew (Apress, 2012)
Silverlight is a framework for building rich, browser-hosted applications that run on a variety of operating systems. Silverlight works its magic through a browser plug-in. When you surf to a web page that includes some Silverlight content, this browser plug-in runs, executes the code, and renders that content in a specifically designated region of the page. The important part is that the Silverlight plug-in provides a far richer environment than the traditional blend of HTML and JavaScript that powers ordinary web pages. Used carefully and artfully, you can create Silverlight pages that have interactive graphics, use vector animations, and play video and sound files.